2005
DOI: 10.1177/1534735404273723
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Breast Cancer Survivors’ Use of Complementary Therapies: Perceived Impact on Recovery and Prevention of Recurrence

Abstract: Results: Most of the respondents were older than 50, were Caucasian, were married, had attended or completed college, and were at least 5 years after breast cancer treatment. The most commonly used CTs included exercise, vitamins, prayer/spiritual practice, support groups, humor, self-help books, and relaxation. These survivors used CT therapies because they wanted to play a more active role in their cancer recovery, to manage stress, and to maintain hope. A majority of them reported that they used CT to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 36 publications
4
57
0
5
Order By: Relevance
“…In this study, women with breast cancer perceived that CAM plays a supportive role for patients with cancer and this is consistent with the findings of international studies which have identified symptom/side effect relief (Cui et al, 2004, Hann et al, 2005, Lengacher et al, 2006, Molassiotis et al, 2006, psychological stress relief (Hann et al, 2005;Henderson & Donatelle, 2004;Lengacher et al, 2006) and a desire for greater control (Chen et al, 2008;Cui et al, 2004;Hann et al, 2005, Henderson & Donatelle, 2004 as the primary reasons for CAM use among women with breast cancer. Importantly, in allowing patients to provide greater detail regarding their experience of CAM therapies and their perceptions of the role of CAM, this study has allowed greater insight into the significance of CAM for patients.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, women with breast cancer perceived that CAM plays a supportive role for patients with cancer and this is consistent with the findings of international studies which have identified symptom/side effect relief (Cui et al, 2004, Hann et al, 2005, Lengacher et al, 2006, Molassiotis et al, 2006, psychological stress relief (Hann et al, 2005;Henderson & Donatelle, 2004;Lengacher et al, 2006) and a desire for greater control (Chen et al, 2008;Cui et al, 2004;Hann et al, 2005, Henderson & Donatelle, 2004 as the primary reasons for CAM use among women with breast cancer. Importantly, in allowing patients to provide greater detail regarding their experience of CAM therapies and their perceptions of the role of CAM, this study has allowed greater insight into the significance of CAM for patients.…”
Section: Discussionsupporting
confidence: 80%
“…Six of these, published in 1999 to 2001, [14][15][16][17][18][19] are summarized in an article by Lengacher et al 20 An additional review of 13 studies published from 2002 to 2006 is summarized in Table 1. [21][22][23][24][25][26][27][28][29][30][31][32][33] Upon review, certain patterns, associations, and predictors of CAM use emerge as commonalities for women with breast cancer. In all of the studies that examined demographic associations with CAM use, women were younger 14,21 and had more education.…”
Section: Complementary and Alternative Medicine Use For Breast Cancermentioning
confidence: 99%
“…21,22 Most studies involve patients in active treatment, 11,18,20,[22][23][24] although a small number have explored CM use among limited groups of survivors. 5,15,25,26 Although this information is valuable, little research has explored CM use by survivors of less common cancers or those not treated at major cancer centers. Population-based information on the prevalence and demographic associations of CM use by cancer survivors can influence clinicians' priorities in informing their patients regarding the benefits and risks of CMs, can help prioritize research investigating the efficacy and safety of CMs, and might guide educational outreach to population segments with low utilization of evidence-based CM interventions.…”
mentioning
confidence: 99%
“…Typically, sample sizes are relatively small and inadequately powered for multivariable analyses of factors associated with patterns of use. Many studies have focused on a single cancer type, primarily breast [14][15][16][17] or prostate cancer, [18][19][20] or a small number of the most common cancer types. 21,22 Most studies involve patients in active treatment, 11,18,20,[22][23][24] although a small number have explored CM use among limited groups of survivors.…”
mentioning
confidence: 99%